Supervivencia y crecimiento de plántulas de Jacaratia mexicana inoculadas con hongos micorrícico arbusculares dentro de un bosque tropical seco - Zulueta-Rodríguez, Ramón; Hernandez-Montiel, Luis G.; Murillo-Amador, Bernardo; Córdoba-Matson, Miguel V.; Lara, Liliana; Alemán Chávez, Isabel (Instituto de Ecología, A.C., 2015)
Survival and growth of Jacaratia mexicana seedlings inoculated with arbuscular mycorrhizal fungi in a tropical dry forestJacaratia mexicana is not only an endemic and typical tropical dry forest tree of Mexico, it is considered as a direct ancestor of the papayo (Carica papaya). Locally it is mainly used in traditional medicine, for human food or for feeding backyard animals (forage plant), but its use value is very restricted or even unknown. Nevertheless, various abiotic and anthropogenic pressures in its Mexican habitat are causing populations of this tree to decline alarmingly. Arbuscular mycorrhizal fungi (AMF) are microorganisms that have an important role for the regeneration of tree species by increasing their ability to absorb water and nutrients. The aim of this study was to determine the effect of AMF on growth and survival of seedlings of J.mexicana transplanted within a fragmented area of the remaining dry forest located in the central portion of the state of Veracruz. We measured height, stem diameter, number of leaves, percent seedling survival and mycorrhizal colonization. Results showed increases in all growth-related variables when seedlings were inoculated with AMF. The results suggest that micosymbionts can play a critical role for the regeneration of J.mexicana and possibly other species of tree within the dry forest, especially helping this endemic species that is currently surviving in a fragmented environment under unfavorable conditions of low availability of water and nutrients.